Audit Quality dan Value Relevance of Accounting Information - Setiawan, Yan Christianto; Mettan, Santho Vlennery (E-Jurnal Akuntansi, 2023)
Users of financial reports need relevant information as a basis for making decisions. The existence of an auditor helps investors in assessing the quality of accounting information. The research aims to examine the quality of audit reports as proxied by the size of the public accounting firm and audit opinions on the value relevance of accounting information. The research population is all sectors of business entities registered on the IDX in the 2018-2021 period. A total of 1,480 observations were used as samples in the research. Researchers use a fixed effect model in a panel data structure to test hypotheses. The research results show that auditor size increases the relevance of earnings value, but reduces the relevance of book value. Meanwhile, the audit opinion was found not to affect the relevance of accounting information. The research findings are interesting because audit opinions provided by Big 4 auditors increase the relevance of book value. This research is expected to help investors consider audit quality as an integral part of fundamental analysis, as well as contribute to the development of the topic of value relevance of accounting information and audit quality . Keywords: Audit, Financial Statement, Value Relevance